Bridging gaps: the role of gender and team composition in collective intelligence within STEM education - Francisca Beroíza-Valenzuela; Natalia Salas-Guzmán; David Huepe (Cogent Education)
This study examines the impact of gender dynamics and team composition on collective intelligence (CI) in STEM higher education, addressing performance variability in individual and collaborative tasks. Using a sequential explanatory mixed-methods design, quantitative data from 102 students were analyzed utilizing non-parametric tests (Wilcoxon rank-sum, Kruskal–Wallis, and Dunn's test for post-hoc comparisons), whereas qualitative analyses, including content analysis of video-recorded triads, provided insights into interaction patterns and gender roles. The quantitative findings demonstrated significant sex and gender-based differences in individual performance (p < 0.05), but no significant differences in collaborative performance (p > 0.05), indicating that teamwork mitigates individual disparities. Teams with a majority of men achieved higher average scores (M = 79.5) but exhibited greater variability compared to those with a majority of women (M = 77.1). Qualitative findings revealed that teams with a majority of women prioritized inclusivity and consensus, whereas those with a majority of men demonstrated negotiation-driven interactions and greater variability in participation. Although collaboration enhances group performance, gendered interaction patterns continue to influence team dynamics. These results underscore the necessity for interventions to foster equitable and inclusive teamwork in STEM, highlighting the pivotal role of collective intelligence in addressing performance disparities.